2021
DOI: 10.1177/02692155211010372
|View full text |Cite
|
Sign up to set email alerts
|

Effect of dual-task training on balance in patients with multiple sclerosis: A systematic review and meta-analysis

Abstract: Objective: To evaluate the effects of dual-task training on static and dynamic balance in patients with multiple sclerosis. Data sources: PubMed/MEDLINE, EMBASE, Scopus, and PEDro databases were searched from inception to March 1, 2021. Methods: This study was conducted in agreement with Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guidelines. Two reviewers assessed studies for inclusion and extracted data. We used the Physiotherapy Evidence Database scale to evaluate the methodo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(9 citation statements)
references
References 40 publications
0
9
0
Order By: Relevance
“…The statistical analysis showed that exercise interventions moderately improved the walking distances immediately after the end of treatment, losing effect 4 and 6 weeks later. The addition of tDCS appeared to provide an ameliorative effect, with significant increases in the distances walked by patients in the experimental group at T1, as in a recent review [ 35 ], and significant increases in BBS for people with MS [ 75 ]. At 4 weeks after the end of the treatment, we found a loss of gain compared to T1, considering that it was significantly lower in the experimental group than in the control group.…”
Section: Discussionmentioning
confidence: 81%
“…The statistical analysis showed that exercise interventions moderately improved the walking distances immediately after the end of treatment, losing effect 4 and 6 weeks later. The addition of tDCS appeared to provide an ameliorative effect, with significant increases in the distances walked by patients in the experimental group at T1, as in a recent review [ 35 ], and significant increases in BBS for people with MS [ 75 ]. At 4 weeks after the end of the treatment, we found a loss of gain compared to T1, considering that it was significantly lower in the experimental group than in the control group.…”
Section: Discussionmentioning
confidence: 81%
“…The aim of this task is to challenge attentional capacity: The ability to walk and retain information in working memory at the same time. Dual task-exercising has been investigated in several studies, showing benefits on balance outcomes in multiple populations such as older adults and persons with neurological disorders (Fritz et al, 2015 ; Ghai et al, 2017 ; Martino Cinnera et al, 2021 ). The benefits are believed to arise from increased automatization of the motor task, and less need for executive resources (Clark, 2015 ; Fritz et al, 2015 ).…”
Section: Discussionmentioning
confidence: 99%
“…The volume and quality of research on exercise interventions among people with MS has improved considerably, and there is now more evidence for the benefits of exercise in MS than any other neurological condition [36]; this may be due to the strong evidence for the safety of exercise in MS [37]. For persons with MS, exercise can improve physical fitness [38][39][40], walking mobility [41][42][43], strength [43,44], balance [45,46], cognition [47], fatigue [40,[48][49][50][51][52][53], depressive symptoms [54][55][56] and quality of life [57,58]. There is evidence indicating that exercise has a positive effect on the hippocampus [59,60], sleep quality [61,62] and cardiovascular and metabolic comorbidity [63][64][65].…”
Section: Growth Of Clinical Trials and Expanding Knowledge Of Benefitsmentioning
confidence: 99%